(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
As R.K.Narayan, a great novelist and story writer of Indo-Anglian Literature depicts Indian sensibility and caste system in most of his novels. Similarly Raja Rao describes social, Political and religious picture of India in his famous novel Kanthapura. He exhibits the significant influence of Mahatma Gandhi on the people of South India. The whole story of the novel presents the reality of Indian village Kanthapura. The novelist also highlights how a Brahmin becomes an outcast among the Brahmin community with his efforts against untouchability